2015
DOI: 10.1002/anie.201503041
|View full text |Cite
|
Sign up to set email alerts
|

A Cell‐Permeable ATP Analogue for Kinase‐Catalyzed Biotinylation

Abstract: ATP analogs have been powerful tools in the study of kinase-catalyzed phosphorylation. However, the cell impermeability of ATP analogs has largely limited their use to in vitro lysate-based experiments. Here we report the first cell permeable ATP analog, ATP-polyamine-biotin (APB). APB promoted biotin labeling of kinase substrates in live cells. APB has future application in phosphoprotein purification and analysis. More generally, these studies provide a foundation for development of additional cell permeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…19 Among these analogs, ATP-biotin (Figure 1b) is an attractive probe for characterizing phosphorylation by affixing a biotin handle onto phosphoproteins, which can be used for subsequent visualization. 20, 21 In addition, kinase-catalyzed biotinylation coupled with avidin affinity purification offers a powerful phosphoprotein enrichment strategy. 22 …”
Section: Introductionmentioning
confidence: 99%
“…19 Among these analogs, ATP-biotin (Figure 1b) is an attractive probe for characterizing phosphorylation by affixing a biotin handle onto phosphoproteins, which can be used for subsequent visualization. 20, 21 In addition, kinase-catalyzed biotinylation coupled with avidin affinity purification offers a powerful phosphoprotein enrichment strategy. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is expected that triphosphate modifications, which gave rise to the 8‐halogenated‐7‐deazadGTP derivatives, could result in candidates for antitumor activity by targeting hMTH1. In future work, 8‐halogenated‐7‐deazadGTP modifications, including nucleotide diphosphate or triphosphate prodrug approach, will be completed to allow the compounds to penetrate cells . Evaluation of nucleotide kinase and DNA polymerase activities are also ongoing.…”
Section: Methodsmentioning
confidence: 99%
“…A fully orthogonal system-in which the engineered enzyme utilizes the bumped substrate analog with high efficiency, while no longer recognizing the native substrate-may also benefit from a high signal-to-noise ratio. The bump-hole strategy has been successful with other enzyme families, including kinases, 30,31 acetyltransferases, 32 methyltransferases, 33 and ADPribosyltransferases. 34 Previous studies have demonstrated that glycosyltransferases are amenable to enzyme-substrate engineering, wherein the active site is modified to accept a non-native substrate.…”
Section: Introductionmentioning
confidence: 99%